The Social Life of African Trypanosomes. Issue 10 (October 2015) - Imhof, Simon; Roditi, Isabel
<x xml:space="preserve">Abstract</x> The unicellular parasite Trypanosoma brucei shuttles between its definitive host, the tsetse fly, and various mammals including humans. In the fly digestive tract, T. brucei must first migrate to the ectoperitrophic space, establish a persistent infection of the midgut and then migrate to the salivary glands before being transmitted to a new mammalian host. In 2010, it was shown that insect stages of the parasite (procyclic forms) exhibit social motility (SoMo) when cultured on a semi-solid surface, and it was postulated that this behaviour might reflect a migration step in the tsetse fly. Now, almost 5 years after the initial report, several new publications shed some light on the biological function of SoMo and provide insights into the underlying signalling pathways.